Narasi Foto: Kehidupan Sosial Masyarakat Ulu Rawas Masa Kolonial Belanda 1825-1942 - Supian Ramli; Lagut Bakaruddin (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2020)
The photos are used as a source of historical writing stored in the KITLV documentation center. Likewise with Ulu Rawas during the Dutch East Indies, most of the description of Ulu Rawas during the colonial period can be found in the KITLV collection photo. Some of these photos depict the life of Ulu Rawas society at that time which consisted of various aspects of life. The purpose of this paper is to look at the history of Ulu Rawas community life in the colonial period through photo narration. The research method used is the Historical research method which consists of five stages of writing which cover: (1) Determination of Themes / Topics, (2) Heuristics, (3) Criticism of Sources, (4) Interpretation, and (5) Historiography. The results of this research show that Ulu Rawas was very existent at that time, a clan area under Onder Afdeling Rawas, Afdelingen Paelembangache Boven Landen, Residency of Palembang, the Dutch East Indies. Most of the photo narratives realized Ulu Rawas's social, geographical, and natural conditions at that time. So it can be concluded that Ulu Rawas during the reign of the Dutch East Indies was one of the regions in the Palembang Residency region which was very calculated especially with the results of its natural wealth for the Dutch East Indies government.